Efficacy of kinesthesia and balance exercise for patients with tibiofemoral arthritis - C.SAIPRIYA,; KAMALAKANNAN.M, (International Journal of Pharma and Bio Sciences, 2017)
Osteoarthritis also known as degenerative arthritis, degenerative joint disease, it occurs in the age of above 40 years and in both the genders. Osteoarthritis is a common arthropathy of the knee. In India, the prevalence of the disease in the adult rural population is estimated to be 5.8%.It is a type of joint disease that results from breakdown of joint cartilage and underlying bone.Investigate the efficacy of kinaesthesia and balance exercises for patients with tibiofemoralarthritis.To evaluate the effects of kinesthesia and balance exercise in reducing the pain for patients with tibiofemoral arthritis. To evaluate the effect of kinesthesia and balance exercise in reducing functional disability for patients with tibiofemoral arthritis. 30 Patients with tibiofemoral arthritis were selected based on the inclusion and exclusion criteria.Conclusion: From the result, it has been concluded that kinaesthesia and balance exercises with interferential therapy Group A is more effective than interferential therapy (Group B) in reducing pain and functional disability.Result: The post test mean value of WOMAC in Group A is 0.93 (SD0.80) and post mean value of WOMAC in Group B is2.20 (0.56) this shows that Group B is greater than Group A with P value (0.0001).